2020
DOI: 10.1155/2020/5397838
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Application of Quality Control Circle in Promoting the Use of Rubber Dams in the Root Canal Treatment of Primary Teeth

Abstract: Objective. Study the effect of quality control circle (QCC) in promoting the usage of rubber dams (RD) in root canal treatment of chronic pulpitis in primary teeth. Methods. Set up a quality control group to increase the amount of rubber dams used in the treatment of chronic pulpitis in primary teeth. Monthly monitoring results of the usage amount were counted by the outpatient computer system. Relevant data were collected through questionnaires, and causes of low utilization were analyzed, and the improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Infelizmente, a literatura destaca que pouco se sabe sobre as atitudes que os cirurgiões-dentistas, em geral, têm acerca do uso de barragens de borracha e outros métodos de isolamento. 2 Isso pode refletir, até certo ponto, o impacto do ambiente profissional 29 , currículos de graduação e pós-graduação, diretrizes educacionais e regulamentos governamentais sobre as atitudes e preferências desses profissionais em um país específico 3 . Na pesquisa em questão, os resultados demonstraram que os dentistas brasileiros têm, em sua grande maioria (55,3%), total domínio do uso do isolamento absoluto, podendo lidar com diversas situações que exige seu uso na prática clínica.…”
Section: Discussionunclassified
“…Infelizmente, a literatura destaca que pouco se sabe sobre as atitudes que os cirurgiões-dentistas, em geral, têm acerca do uso de barragens de borracha e outros métodos de isolamento. 2 Isso pode refletir, até certo ponto, o impacto do ambiente profissional 29 , currículos de graduação e pós-graduação, diretrizes educacionais e regulamentos governamentais sobre as atitudes e preferências desses profissionais em um país específico 3 . Na pesquisa em questão, os resultados demonstraram que os dentistas brasileiros têm, em sua grande maioria (55,3%), total domínio do uso do isolamento absoluto, podendo lidar com diversas situações que exige seu uso na prática clínica.…”
Section: Discussionunclassified
“…Rubber dam is unanimously accepted as an essential aide in dental treatment as it provides efficient moisture control. 1 Rubber dam usage is promoted by many authorities and clinicians are encouraged to accept it in regular dental practice as it is a necessary component of current dental service [2][3][4] . Rubber dam offers visibility during treatment by retraction and protection of soft tissues, in addition, it provides a sterile operating field 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It reduces the risk of infections for the dentists and dental assistants. Patients can be protected from aspiration and ingestion of small instruments, medicaments and irrigating solutions used during endodontic treatment 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%